2021
DOI: 10.1111/ijcp.14621
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 confinement and related well being measurement using the EQ‐5D questionnaire: A survey among the Palestinian population

Abstract: Purpose This study aims to assess the effect of the COVID‐19 confinement on the population wellbeing using the EQ‐5D questionnaire. Methods After receiving the written permission from the EuroQol Research Foundation, an online‐based survey was prepared and a total of 1380 participants were recruited via social media. The relationships of all the factors were studied as well as the scores of the EQ‐5D including EQ‐5D Index, Visual Analogue Scale (VAS), and each of the EQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…According to our study, comorbidity, especially asthma (Table 4 ), is significantly associated with lower health utility scores (Table 2 ). This similar with studies from Vietnam [ 26 ], Palestine [ 27 ], Peru [ 28 ], India [ 29 ] and Addis Ababa, Ethiopia [ 30 ]. The mean VASscores were significantly lower for respondents with comorbidity (62) than for those without it (75) ( p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to our study, comorbidity, especially asthma (Table 4 ), is significantly associated with lower health utility scores (Table 2 ). This similar with studies from Vietnam [ 26 ], Palestine [ 27 ], Peru [ 28 ], India [ 29 ] and Addis Ababa, Ethiopia [ 30 ]. The mean VASscores were significantly lower for respondents with comorbidity (62) than for those without it (75) ( p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…In general, comorbidities (such as hypertension, chronic cardiac diseases, chronic pulmonary disease, asthma, chronic kidney disease and diabetes mellitus) were significantly associated with low HSU VAS scores. Studies from Vietnam (70.8 vs 63.3) [ 31 ], China (97.9 Vs 82.8) [ 20 ] and Palestine (80 vs 70) [ 27 ] revealed that individuals with chronic diseases have a lower HRQOL than those without comorbid disease, perhaps because those with comorbidities develop anxiety or depression in response to misinformation disseminated about the impact of the virus in these communities [ 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the finding from Vietname, 0.95, 17 China, 0.949, 48 and greater than the study conducted in Vietnam,0.66, 49 Hong Kong, 0.897, 50 Norway, 0.82, 51 Iran, 0.6125, 52 and Palestine, 0.65. 53 The observed discrepancy was might be due to the difference in tariff value used, method of measurement, study period, study population, and comorbidities. In our study, pain/discomfort (49.1%) and anxiety/depression (54.6%) were the two commonly impaired dimensions of EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies that found a decreased EQ-5D score with increasing age of Covid-19 patients. 48 , 52 , 53 , 63 This might be due to psychological stress as a result of news about Covid-19, increased comorbidity, and deterioration of the physical condition of older people. 64 , 65 The associations between lower HRQoL and prolonged hospitalization, as well as health status at admission in our study, were also consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Palestine, the lockdown measures were adopted between March 2020 and August 2021 through which the universities were nearly closed. There are few studies on the psychological impact of the pandemic on the general Palestinian population [ 3 , 4 ] and among school students [ 5 ]. In both cases, the levels of depression and anxiety were reported to be high in most of the studied populations.…”
Section: Introductionmentioning
confidence: 99%